Ziyadah from an Islamic Perspective (Case study at BMT Al-Rifa’ie) - Absari, Dyatri Utami Arina; Kholili, Isa (Privietlab, 2024)
Islamic banking principles emerge primarily from the unequivocal prohibition of riba (usury) in the Quran. The Indonesian government has bolstered Islamic banking with legal frameworks, beginning with Law No. 7 of 1992, later replaced by Law No. 10 of 1998, providing a robust legal basis for its operations. The evolution of Islamic banking in Indonesia started with the establishment of Bank Muamalat Indonesia (BMI) on November 1, 1991, which catalyzed the rise of Islamic financial institutions such as Baitul Maal Wa Tamwil (BMT). Interest (riba) is forbidden in Islam due to the additional or ziyadah interest charged on loan transactions. BMT, operating as an Islamic financial institution, eschews interest in favor of profit-sharing systems. The Indonesian Ulema Council (MUI) has issued several fatwas related to ziyadah, including MUI Fatwa No. 1 of 2004. This research, conducted at BMT Al-Rifa’ie, adopts a qualitative approach with a historical hermeneutic analysis. Informants include seven individuals from management, customers, and the MUI. The study concludes that the ziyadah practices at BMT Al-Rifa’ie align with Islamic principles.